Recent progress in cowpea breeding - Singh, B.B.; Ehlers, J.D.; Sharma, B.; Freire Filho, F.R. (2002)
Considerable progress has been made in breeding improved cowpea varieties in the last five years. The major breeding objectives were to develop high yielding cowpea varieties for sole cropping as well as intercropping with acceptable seed types and resistance to major diseases, insect pests, nematodes, and the parasitic plants Striga and Alectra and tolerance to heat and drought. Good progress was also made in breeding early maturing grain type, dual pupose, and fast growing fodder type cowpea varieties. The informal network of world cowpea researchers catalyzed by IITA and the Bean/Cowpea Collaborative Research Support Program has been very effective in evaluating and selecting improved cowpea varieties for a wide range of environments. As a consequence, total world has substantially increased.